The Necessity and Development of Rural Physical Education in the Context of Rural Revitalization—Taking Rural Physical Education in Henan Province as an Example - Wang, Jingxuan; Fan, Hong (Journal of Research in Vocational Education, 2025)
The fundamental purpose of rural revitalization is to enhance the quality of life for hundreds of millions of farmers. Strengthening rural education and expanding sports programs in villages serve as crucial tools for implementing the rural revitalization strategy, effectively improving farmers ‘livelihoods. Village sports education focuses on integrating local resources to develop distinctive cultural programs, upgrading infrastructure, and integrating physical activities into daily life. This approach ensures better health and mental well-being while optimizing rural living conditions. This paper first analyzes the necessity of rural sports education under the rural revitalization framework, examining both its shortcomings and advantages in Henan’s context. Subsequently, it explores future development strategies through multiple dimensions including urban-rural resource coordination, organizational structures, cultural development, operational models, and grassroots governance mechanisms.